Relationship between mood states, exercise behaviour, coping and mental health among Malaysian during covid-19 pandemic by using path analysis - Mun, Yew Jing (2021)
Coronavirus disease or COVID-19 is a serious infection that not only make an impact on physical health, it also affects mood states, exercise behaviour and coping which in turn to affect mental health status among Malaysian during COVID-19 pandemic. This study is aimed to determine the relationship of mood state, exercise behaviour, coping and mental health among Malaysian by using path analysis and their changes from Wave-2 to Wave-3 phases of COVID-19 pandemic. A cross-sectional study was conducted using self-administered questionnaires via an online survey. Snowball sampling and convenience sampling method were used to recruit respondents during Wave-2 and Wave-3 survey, respectively. Ministry of Health Malaysia announced the second wave of COVID-19 cases started on 27 February 2020 and third wave started on 20 September 2020. The questionnaires of Brunel Mood Scale (BRUMS), Exercise Regulations in Exercise-3 (BREQ-3), Brief Coping Orientation of Problem Experienced (COPE) and Depression, Anxiety and Stress Scale (DASS-21) were used. Path analysis and paired t test were conducted for statistical analyses. A total of 842 and 329 respondents participated in the survey during Wave-2 and Wave-3, respectively. The final path model revealed path model has a good fit: Comparative Fit Index (CFI) = 0.998, Tucker-Lewis Index (TLI) = 0.988, Standardised Root-Mean Square Residual (SRMR) = 0.001, Root Mean Square Error of Approximation (RMSEA) (90%CI) = 0.072 (0.056, 0.088), RMSEA p-value = 0.012. There were significant path relationship between mood, exercise behaviour, coping and mental health, with total of 36 paths were supported and statistically significant, and additional five new paths were statistically significant and theoretically important. The variables mood, exercise behaviour and coping were also showed to have direct and indirect effects on mental health. Besides, the study revealed that there were significant mean difference between Wave-2 and Wave-3 on negative mood, introjected regulation, integrated regulation, intrinsic regulation and depression scores. Findings of this study reported that mental health may be improved by enhancing mood, exercise behaviour and coping (directly and indirectly). There are also significant changes between Wave-2 and Wave-3 among the variable mood, exercise behaviour and mental health. Therefore, the information obtained would be crucial for proving accurate information in turn to develop an intervention plan to improve mental health status.